Design of Smart Campus using Zigbee based on USN - Byeongtae Ahn, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Universities that have been pursuing informatization with the development of highspeed networks and IoT (Internet of Things) are expanding the informatization area by introducing online academic administration systems, mobile campuses, and electronic libraries as part of the recent smart campus construction. As key technologies in this ubiquitous rank, the Ubiquitous Sensor Network (USN) along with radio frequency identification (RFID) and zigbee are emerging. In this paper, we propose an integrated management system model for the establishment of a smart campus, such as a digital library system and a smart card system capable of providing various services using zigbee, which is currently prominent. The integrated management system can provide a higher quality education environment through transparent and efficient administrative management and one-stop service provision, away from the labor-intensive system of educational institutions, and users can provide personalized and knowledgeable intelligent education services that meet their needs and environments.